Integrasi Pembelajaran Berdiferensiasi pada Kurikulum Modifikasi dalam Mewujudkan Merdeka Belajar di Sekolah Dasar - Monica Wahyu Pertiwi; Anam Sutopo; Choiriyah Widyasari (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to describe the implementation of differentiated learning at SDIT Muhammadiyah Al Kautsar and describe the obstacles of teachers in implementing this differentiated learning process at SDIT Muhammadiyah Al Kautsar. This research uses qualitative with descriptive research type. The source of this research is the 5th grade teacher at SDIT Muhammadiyah Al Kautsar. Data collection was done through interviews, observation, and document review. Data analysis techniques used in this research are data reduction, data presentation, and verification. The results showed that the implementation of differentiated learning in grade 5 SDIT Muhammadiyah Al Kautsar was carried out based on the principles of differentiated learning including: 1) learning environment, namely seeing how the student's classroom environment, 2) continuous assessment, namely measuring the extent of student readiness in learning, 3) responsive learning, namely how teachers can understand various kinds of student characters and student deficiencies in learning, and 4) class routines, namely how the results of student learning with the leadership of the class teacher, which have been carried out well. The conclusion of this research is that differentiated learning focuses on students so it is feasible to implement in a modified curriculum. The obstacle of differentiated learning is that the teacher is a little difficult to adapt to the student's personality during learning. Solution to the obstacles faced